Comparison of two pedaling sensors, I-Crankset and SRM, against a standard reference sensor - Bernard, J.; Decatoire, A.; Lacouture, P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Our aim was i) to validate the I-Crankset sensor (I-CS) with a reference torque sensor (RTSL) for the calculation of crankset torque, power and work outputs and ii) to compare I-CS with the SRM sensor, a popular device. SRM and I-CS sensors were mounted simultaneously on a test bench instrumented with the RTSL used to validate I-CS. The protocol included multiple sets of 30 pedaling cycles in three conditions to explore various solicitations. Torque magnitudes, angular velocity and power output were compared using the coefficient of multiple correlation inter-protocol. The results showed a good validity of both the I-CS and SRM for all the conditions in comparison to RTSL for torque`s measurements and power`s calculations, even if an average angular velocity is used by SRM. But this one showed its limitations when calculating the work output.